A situational picture of HIV/AIDS and injection drug use in Vinnitsya, Ukraine - Dumchev Kostyantyn; Schumacher Joseph E; Barcal Katerina; Moroz Larisa (BMC, 2005)
Abstract Background New and explosive HIV epidemics are being witnessed in certain countries of Eastern Europe, including Ukraine, as well as a rapid and dramatic increase in the supply, use, and negative public health consequences of illicit drugs. A majority of registered HIV cases in Ukraine occur among injection drug users (IDUs), large numbers of whom report HIV risk behaviors such as needle sharing. The purpose of this study was to apply the World Health Organization's Rapid Assessment and Response on Injection Drug Use (IDU-RAR) guide to create a situational picture in the Vinnitsya Oblast, Ukraine, a region with very scarce information about the HIV/AIDS and injection drug use (IDU) epidemics. Methods The IDU-RAR uses a combination of qualitative data collection techniques commonly employed in social science and evaluation research to quickly depict the extent and nature of the given health problem and propose locally relevant recommendations for improvement. The investigators focused their assessment on the contextual factors, drug use, and intervention and policy components of the IDU-RAR. A combination of network and block sampling techniques was used. Data collection methods included direct observation, review of existing data, structured and unstructured interviews, and focus group discussions. Key informants and locations were visited until no new information was being generated. Results The number of registered HIV cases in Vinnitsya has increased from 3 (1987-1995) to 860 (1999-10/2004), 57 of whom have already died. Ten percent of annual admissions to the area's Regional Narcological Dispensary were for opiate disorders, and the number of registered IDUs rose by 20% from 1999 to 2000. The level of HIV/AIDS awareness is generally poor among the general population but high among high-risk populations. Both HIV/AIDS and injection drug use carry a strong stigma in the community, even among medical professionals. There was very little evidence of primary HIV/AIDS prevention efforts, and IDU prevention efforts focused on promotion of anti-drug messages in the schools. Conclusion Given that Ukraine has sparse resources to be devoted to this problem, action recommendations should be prioritized, realistic, and initially targeted to persons in greatest need. The following action recommendations are prioritized by the following categories: First priority: Voluntary Counseling and Testing; Second Priority: Prevention and Education; and Third Priority: Harm Reduction and Treatment. They are provided in this sequence based on what response can realistically be implemented first with limited additional resources and can make the greatest immediate impact. The persons at greatest risk, HIV positive persons and IDUs, should be attended to first.